Characterization of type II thioesterases involved in natamycin biosynthesis in Streptomyces chattanoogensis L10. Issue 17 (23rd July 2014) - Wang, Yue-Yue; Ran, Xin-Xin; Chen, Wei-Bin; Liu, Shui-Ping; Zhang, Xiao-Sheng; Guo, Yuan-Yang; Jiang, Xin-Hang; Jiang, Hui; Li, Yong-Quan
Abstract : The known functions of type II thioesterases (TEIIs) in type I polyketide synthases (PKSs) include selecting of starter acyl units, removal of aberrant extender acyl units, releasing of final products, and dehydration of polyketide intermediates. In this study, we characterized two TEIIs (ScnI and PKSIaTEII) from Streptomyces chattanoogensis L10. Deletion of scnI in S. chattanoogensis L10 decreased the natamycin production by about 43%. Both ScnI and PKSIaTEII could remove acyl units from the acyl carrier proteins (ACPs) involved in the natamycin biosynthesis. Our results show that the TEII could play important roles in both the initiation step and the elongation steps of a polyketide biosynthesis; the intracellular TEIIs involved in different biosynthetic pathways could complement each other. Abstract : Two intracellular TEIIs, ScnI and PKSIaTEII, complement each other. ScnI removes aberrant extender units in elongation steps of natamycin biosynthesis. ScnI removes unfavored starter units in initiation step of natamycin biosynthesis.